Kajian Penentuan Standart Kebutuhan Ruang Parkir Hotel Berbintang di Kota Semarang - Ismiyati, Ismiyati (MEDIA KOMUNIKASI TEKNIK SIPIL, 2004)
Star hotel infrastruktur must support by good facility and well services,one for example to provide parking facility that sufficient  for the guess at the  hotel. This study hopely can determine the standart of parking star hotel needs involving with hotel parameters and to determine reduction coefficient of parking hotel needs involving with guest hotel that do trip with many purpose. In this study the location of four hotels that will observe are  Patra Jasa Hotel at  Jl.Sisingamangaraja, Graha Santika Hotel at Jl.Pandanaran, Santika Hotel at Jl.Ahmad Yani and Metro Hotel at Jl. Johar Baru Semarang. This research with approuch  Regresi analisis method,it is look for correlasion amount variable visitor Hotel with variable of hotel facilities. A comparison between parking needs of the guest hotel  parameters which are:1 parking space for  1.54 - 1.86 guest of ballroom,1 parking space for 1.88 - 2.08 room available, and 1 parking space for 78.86 - 79.06 squarre meter hotel floor.Variety for each hotel ,At Patra Jasa Hotel value around are 0.55 – 0.79,for Graha Santika Hotel are 0.67 – 0.86,for Santika Hotel are 0.68 – 0.81 and for Metro Hotel are 0.73 – 0.91 . Variation of the reduction coefficients happens because of guest activity to the different facilities hotel that observed and a difference in serving for hotel facilities that available for guests. Keywords: Standard, parking, hotelPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/2768[How to cite: Ismiyati, 2004, Kajian Penentuan Standart Kebutuhan Ruang Parkir Hotel Berbintang di Kota Semarang, Jurnal Media Komunikasi Teknik Sipil, Volume 12, Nomor 3, pp. 49-59]